The Aesthetics of Failure : Inexpressibility in Samuel Beckett's Fiction. - Tereszewski, Marcin (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
Although Beckett scholarship has in recent decades experienced a renaissance as a result of various poststructuralist approaches that tend to emphasize destabilization and inexpressibility as the defining features of Beckett's output, relatively little attention has been paid to the ethical aspects of his aesthetics of failure. This book fits into that renaissance, but draws on a distinct, though rarely addressed, connection that Samuel Beckett's work shares with that of Maurice Blanchot and ...
Table of contents; acknowledgements; introduction; chapter one; chapter two; chapter three; conclusion; bibliography; index.
Print version record.
eBooks on EBSCOhost
Keywords: Beckett, Samuel, -- 1906-1989 -- Aesthetics; Beckett, Samuel, -- 1906-1989; Aesthetics, Modern -- 20th century; Failure (Psychology) in literature; Esthétique -- 20e siècle.; Échec dans la littérature.; LITERARY CRITICISM -- European -- French; Aesthetics; Aesthetics, Modern; Failure (Psychology) in literature; 1900-1999; Criticism, interpretation, etc